High-Throughput Screening Identifies Genes Required for Candida albicans Induction of Macrophage Pyroptosis - Teresa R. O’Meara (American Society for Microbiology, 2018)
ABSTRACT The innate immune system is the first line of defense against invasive fungal infections. As a consequence, many successful fungal pathogens have evolved elegant strategies to interact with host immune cells. For example, Candida albicans undergoes a morphogenetic switch coupled to cell wall remodeling upon phagocytosis by macrophages and then induces macrophage pyroptosis, an inflammatory cell death program. To elucidate the genetic circuitry through which C. albicans orchestrates this host response, we performed the first large-scale analysis of C. albicans interactions with mammalian immune cells. We identified 98 C. albicans genes that enable macrophage pyroptosis without influencing fungal cell morphology in the macrophage, including specific determinants of cell wall biogenesis and the Hog1 signaling cascade. Using these mutated genes, we discovered that defects in the activation of pyroptosis affect immune cell recruitment during infection. Examining host circuitry required for pyroptosis in response to C. albicans infection, we discovered that inflammasome priming and activation can be decoupled. Finally, we observed that apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization can occur prior to phagolysosomal rupture by C. albicans hyphae, demonstrating that phagolysosomal rupture is not the inflammasome activating signal. Taking the data together, this work defines genes that enable fungal cell wall remodeling and activation of macrophage pyroptosis independently of effects on morphogenesis and identifies macrophage signaling components that are required for pyroptosis in response to C. albicans infection. IMPORTANCE Candida albicans is a natural member of the human mucosal microbiota that can also cause superficial infections and life-threatening systemic infections, both of which are characterized by inflammation. Host defense relies mainly on the ingestion and destruction of C. albicans by innate immune cells, such as macrophages and neutrophils. Although some C. albicans cells are killed by macrophages, most undergo a morphological change and escape by inducing macrophage pyroptosis. Here, we investigated the C. albicans genes and host factors that promote macrophage pyroptosis in response to intracellular fungi. This work provides a foundation for understanding how host immune cells interact with C. albicans and may lead to effective strategies to modulate inflammation induced by fungal infections.